Guidance sources at work: The role of sociodemographics in the United States and Brazil (Management and Connections Journal, 2023)
This study aimed to statistically test the influence of employees’ sociodemographic characteristics on their use of sources of guidance at work in the United States and Brazil. To achieve this objective, 220 employees from a Brazilian university and 166 employees from an American university filled out a paper-and-pencil questionnaire comprised of a previously-validated scale. Correlations and multiple linear regressions were run to test this influence. Among other results, American employees with higher education levels are more likely to use Informal Rules as sources of guidance at work. In turn, Brazilian employees with previous experience in managerial positions are more likely to use their Own Experience as a source of guidance at work. The results yielded from the tests suggest to managers, human resource professionals, and psychologists which sociodemographic characteristics are relevant to predicting the use of guidance sources at work, contributing, for instance, to recruitment and selection processes.
Keywords: Sources of guidance; Sociodemographic characteristics; Organizational behavior; Human resources management; Cross-cultural research